News consumption patterns on Twitter: fragmentation study on the online news media network. Issue 10 (October 2020) - Gaol, Ford Lumban; Maulana, Ardian; Matsuo, Tokuro
Abstract: The development of news media and social media has radically changed the way the public consumes information. This study explores the structure of online news media networks in three countries, namely Indonesia, Malaysia and Singapore, to investigate the phenomenon of fragmentation in the news consumption pattern on social media. Based on the results of the three network indicators used in this study, it can be concluded that the structure of online news media networks in Indonesia and Malaysia shows a tendency of fragmentation. In contrast, this study did not find sufficient evidence that the phenomenon of fragmentation was occurring in the Singapore media network. In-depth analysis on each formed media cluster shows that online news media in Indonesia and Malaysia tend to group based on similarity in market segments, regions or political alignments. Abstract : Computer science; Network analysis; Media fragmentation; Online news media; Twitter; News consumption